Higher Education and Development in Kerala - Jandhyala B G Tilak (CSESWP5, 2001)
Despite high levels of literacy, near universal enrolment in elementary education, high levels of social and human development, why could Kerala not transform itself into a prosperous developed state. Why does the state of Kerala lag behind other states in India in economic development? It is argued here that the principal reason for this is the neglect of higher education in the state. Universal elementary education is aworthy goal and is necessary for development of the societies; but it does not provide the wherewithal necessary for economic growth. While reviewing the higher education scene in Kerala, this short paper examines some general premises, which are questionable, but are widely in circulation, and form the basis for policy formulation, relating to `over' expansion of higher education and financing of higher education